Buddha in Sri Lanka : remembered yesterdays - Wickremeratne, Swarna, 1939- (State University of New York Press, 2006)
"This book provides both an erudite and intimate look at how Buddhism is lived in Sri Lanka. While India is known as the birthplace of Buddhism, Sri Lanka is its other home; Buddhism extends back over twenty-five hundred years on the island and remains at the center of its spiritual traditions and culture. Throughout the book, author Swarna Wickremeratne incorporates a personal view, sharing stories of herself, her family, friends, and acquaintances as they "lived Buddhism" both during her Sri Lankan girlhood and during more recent times."--Jacket.